A realist analysis of treatment programmes for sex offenders with intellectual disabilities. Issue 4 (13th May 2019) - Hollomotz, Andrea; Greenhalgh, Joanne
Abstract: Background: The resources used in treatment for sex offenders with intellectual disabilities have had much research attention, but less has been written about how participants are expected to respond (programme mechanisms). Methods: A realist evaluation of seven programmes from the UK, Canada, USA, Switzerland and Germany was conducted. In semi‐structured interviews, programme designers elucidated how they are intended to work. The data analysis was driven by the realist concern to expose programme mechanisms and intended outcomes. Results: Two main outcomes are increasing risk management capacities and cultivating prosocial identities. These are achieved through developing insights into a person's risks, work on (sexual) self‐regulation skills, sexual boundaries and personal values and by developing meaningful social roles and positive relationships. Conclusions: Over time, there have been changes to some of the treatment resources used. However, there were little differences in terms of the intended programme mechanisms and outcomes, which remained surprisingly consistent.